The Impact of Digital Transformation and Innovation Capability on Competitive Advantage: The Mediating Role of Market Orientation in Emerging Markets - Sastra, Eka; Sallatu, Mohammad Afif; Sanusi, Abdullah (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
This study aims to examine the impact of digital transformation and innovation capability on competitive advantage, with market orientation as a mediating variable, particularly within the dynamic conditions of emerging markets. Using a quantitative, cross-sectional design, data were collected from 230 mid- and senior-level managers in Indonesian firms across various industries. The study employed Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test both direct and mediating relationships. Results show that both digital transformation and innovation capability significantly enhance market orientation. In turn, market orientation positively influences competitive advantage and partially mediates the relationships between the antecedent capabilities and performance. These findings underscore market orientation’s central role in translating internal capabilities into strategic outcomes. This study contributes to strategic management literature by integrating digital, innovative, and behavioral resources into a coherent model of competitive advantage. It also addresses a gap in research on the interplay among these constructs in emerging market contexts.